Electrical Homogeneity Mapping of Epitaxial Graphene on Silicon Carbide - Whelan, Patrick R; Panchal, Vishal; Petersen, Dirch H; Mackenzie, David M. A; Melios, Christos; Pasternak, Iwona; Gallop, John; Østerberg, Frederik W; U. Jepsen, Peter; Strupinski, Wlodek; Kazakova, Olga; Bøggild, Peter (ACS applied materials & interfaces, 2018)
Epitaxial graphene is a promising route to wafer-scale production of electronic graphene devices. Chemical vapor deposition of graphene on silicon carbide offers epitaxial growth with layer control but is subject to significant spatial and wafer-to-wafer variability. We use terahertz time-domain spectroscopy and micro four-point probes to analyze the spatial variations of quasi-freestanding bilayer graphene grown on 4 in. silicon carbide (SiC) wafers and find significant variations in electrical properties across large regions, which are even reproduced across graphene on different SiC wafers cut from the same ingot. The dc sheet conductivity of epitaxial graphene was found to vary more than 1 order of magnitude across a 4 in. SiC wafer. To determine the origin of the variations, we compare different optical and scanning probe microscopies with the electrical measurements from nano- to millimeter scale and identify three distinct qualities of graphene, which can be attributed to the microstructure of the SiC surface.